2022
DOI: 10.3748/wjg.v28.i41.5982
|View full text |Cite
|
Sign up to set email alerts
|

High incidence combination of multiple primary malignant tumors of the digestive system

Abstract: BACKGROUND Clinical reports of multiple primary malignant tumors (MPMTs) in the digestive system are increasing. In China, although the survival rate of patients with MPMTs is increasing, the quality of life is very low. Many patients have reached the advanced stage when the second primary tumor is found, resulting in no early intervention and treatment. This is due to the misunderstanding of MPMTs by clinicians, who treat such tumors as metastases. Therefore, before a patient has a second primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Due to the development of screening technologies and diagnostic tools, the detection rate of MPMTs is increasing. Zhai et al found that MPMTs harbored tumors whether in the same organ or in the different organs, the incidence of digestive system malignancies was the highest, 4 and the clinical reports on MPMTS in the digestive system is increasing, 5 but the incidence of synchronous double primary liver cancers is extremely low, about 0.1% to 1%, the most common pathological type was hepatic, neuroendocrine, and biliary components, when synchronous MPMTs occurred in liver independently, they also defined as collision type. 6 The mechanism of tumorigenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the development of screening technologies and diagnostic tools, the detection rate of MPMTs is increasing. Zhai et al found that MPMTs harbored tumors whether in the same organ or in the different organs, the incidence of digestive system malignancies was the highest, 4 and the clinical reports on MPMTS in the digestive system is increasing, 5 but the incidence of synchronous double primary liver cancers is extremely low, about 0.1% to 1%, the most common pathological type was hepatic, neuroendocrine, and biliary components, when synchronous MPMTs occurred in liver independently, they also defined as collision type. 6 The mechanism of tumorigenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This concept was first described in 1989. ( 4 6 ) MPMN is rare in clinical practice, accounting for only 0.52–11.7% of all malignant neoplasms ( 7 ). Based on the time interval between the occurrence of different primary tumors, MPMN can be further classified into (1) synchronous: relatively rare cases in which the intervals between the occurrences of MPMN are < 6 months, and (2) metachronous: common cases in which the intervals between the occurrences of MPMN are ≥ 6 months, ( 8 ) accounting for approximately 90% of MPMN cases.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted the criteria proposed by Warren and Gates in 1932 for the diagnosis of MPMTs: (1) Each tumor must be a pathologically proven as malignant; (2) Each tumor must be histologically distinct; and (3) the possibility of the tumor resulting from the metastasis of another must be excluded[ 1 ]. MPMTs can be sub-classified into either synchronous MPMTs (SMPMTs) and metachronous MPMTs (MMPMTs), according to their time interval, defined as the time between the date of diagnosis of the first primary cancer and the date of diagnosis of the second primary cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple primary malignant tumors (MPMTs) are defined as the coexistence of two or more independent primary malignancies of different histologies in a single patient, either simultaneously or consecutively. MPMT was first described by Billroth as early as 1889, with the first report published by Warren and Gates in 1932[ 1 ]. Since then, numerous cases have been reported.…”
Section: Introductionmentioning
confidence: 99%